2007
DOI: 10.1016/j.jimonfin.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the global pattern of current account imbalances

Abstract: This paper assesses some of the explanations that have been put forward for the global pattern of current account imbalances that has emerged in recent years: in particular, the large U.S. current account deficit and the large surpluses of the Asian developing economies. Based on the approach developed by Chinn and Prasad (2003), we use data for 61 countries during 1982-2003 to estimate panel regression models for the ratio of the current account balance to GDP. We find that a model that includes as its explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
187
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(207 citation statements)
references
References 25 publications
14
187
2
4
Order By: Relevance
“…The current account balance predictors in the analysis are a set of macroeconomic variables that are known to influence the current account balance. They have been selected based on the literature on current account balances and the EMU set out in Section 2 and the previous empirical literature on the economic determinants of current account balances (see for example Chinn and Prasad, 2003;Gruber and Kamin, 2007;Schmitz and von Hagen, 2011). I account for the competitiveness channel by including measures of the price level of exports (relative to the US) and trade openness (%).…”
Section: Datamentioning
confidence: 99%
“…The current account balance predictors in the analysis are a set of macroeconomic variables that are known to influence the current account balance. They have been selected based on the literature on current account balances and the EMU set out in Section 2 and the previous empirical literature on the economic determinants of current account balances (see for example Chinn and Prasad, 2003;Gruber and Kamin, 2007;Schmitz and von Hagen, 2011). I account for the competitiveness channel by including measures of the price level of exports (relative to the US) and trade openness (%).…”
Section: Datamentioning
confidence: 99%
“…For example, the studies of Hatsopoulos et al (1988), Fischer and Easterly (1990), Hakkio (1995), Milesi-Ferretti and Razin (1996), Higgins andKlitgaard (1998), Cooper (2001), Mann (2002), Gale and Orszag (2003), Labonte (2005), Hubbard (2006), Szakolczai (2006), Elwell (2007Elwell ( , 2010 and Feldstein (2008) can be adduced for the theoretical studies about triplet deficit. Some empirical studies on this topic have argued that the triple deficit hypothesis is valid (Zaidi, 1985;Roubini, 1988;Baxter and Crucini, 1993;Eisner, 1994;Freund, 2005;Kuijs, 2006;Gruber and Kamin, 2007). For example, Penati and Dooley (1984), in their study of 19 industrialized countries, demonstrated the validity of the triple deficit hypothesis which emphasizes that imbalances emerge in the current account because of changes in the volume of savings.…”
Section: Literature Review and Theorymentioning
confidence: 99%
“…Kuijs (2006) analyzed data for the period 1980-2005 and found that the triple deficit hypothesis applied in reverse to the Chinese economy and called this a case of 'triple surpluses'. In their study of 61 countries for the period 1982-2003, Gruber and Kamin (2007) stated that globally increasing savings negatively affected economies that experienced a savings gap and thus caused an increase in the current accounts deficit.…”
Section: Literature Review and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we analyse if countries with more developed financial systems attract net capital inflows. 1 While the standard (medium-term) determinants of international capital flow patterns have been prominently established by Chinn and Prasad (2003) and Gruber and Kamin (2007), there is no consensus yet on the role of domestic financial systems for international capital flows.…”
Section: Introductionmentioning
confidence: 99%